A institucionalização política da União Européia - Santiago, Bráulio Junqueira (2007)
The creation of the European Union is, sometimes questioned for some people, a permanent negotioation between its respective State-Members; at the beggining six, then nine, twelve, fifteen, twenty-five and today twenty-seven and tomorrow, we will not know the exact number (Turkey has been agreement tready with European Union and as candidate countries are the States of Russia and Croatia). Each decision presums an agreement. If we have a global overlook, which means, if we look from outstide what happens inside this phenomenon, we realize that this creation brings advantages for all of the twenty-seven State-Members, on the other hand, it is a paradox that for each decision taken by the European Union, can not be an advantage for the twenty-seven States at the same time. Here resides the quid of the pacific permanence of this supernatural phenomenon, in which the twenty-seven States decide it. This difficulty gets greater knowing that the twenty-seven State-Members are, in many aspects deeply unequal. There is no doubt it is found in the Europeon Union´s quotidian interest differences. During the negotioations, each state acts according to the advantages of national interests, sometimes in a selfish way, seeking to take away this atribute of the supranational Union. Behind the visible issues are hidden other reasons that take each of the twentyseven States to desagree with each other. The differences are from many sorts. The proposal of this work is to show that such differences can come from the cultural, sociological, antrophological and sensibility differences... In short, this differences are based on their different historical pasts, the fact of twenty-seven State- Members exist in one same Union. There is a perfect knowlege that the European Union creation is an artificial act of men (differentely of family creations, tribes, cittas, Polis and the State) and nothing that refers to men is that simple. And if we face a relevant historical question which seems simple we can believe that we seek a way to deform it immediately, because the role of the law or history researcher, or even the history of the Juridical thinking is not to simplify the real, but to find out that inside this apparent simplicity, there is the living elements complexity. Inexorably, each State understands Europe and the European Union by their own manners; each one has their action fields' singular view of a plural community. This research could not left out the historical facts that are among the science of the Rights. For example, the history tells that was seen at Paris Conference Paris Peace of 1919 when J.M.Keynes questioned himself: What did this institution get in their golden rooms? In several moments, Keynes censured on his own memorandum prepared for the Paris Conference that the German State could not take a responsability greater than the amount of £2 billions and that any more pound could lead Europe to catastrophical results. So has foreseen Keynes. With this emblematic fact, another question is able to be answered: Could the knowlege of the past help in the construction of the future? If we don't give the correct importance to this context, historical and political, it may be risky to evaluate the situation on a mistaken way. The citizens excluded from this reality, several times because of wrong information or poor formation or even both, link Europe only to its direct narrow environment. This is the reason why for many French, for example, Europe is still the broaden sexangle . However, at any moment the crises may be increased, and at moments of severe crises it is natural to the nationalist asleep feeling to wake up, and take us to a situation in which prevailes the idea of a personal independence. It is necessary to remember that the own European Union´s idea itself, presupposed in advance that each State-Member could hide its apanages; its culture, its identity and by the subsidiary and solidarity s principles from the State-Members or the European Union show themselves capable of avoiding diversions towards extremed nationalism, with the followers of rage and wars, scattering throughout mankind and contaminating the newly discovered small Earth